Fungsi dan Kedudukan Kata Ganti (Dhamir) dalam Ilmu Sharf - Sam, Zulfiah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2018)
Arabic is the language of the Al-Qur'an which was sent down byAllah Almighty. Arabic is a language that has rich vocabularies and itis a language known for its complex grammatical structure(qawa'ed). In order to understand arabic properly, theunderstanding the grammar of the language is necessary. It is anobligation upon the Moslem to learn Arabic for bettercomprehension in Qur'anic text. In this research, the authorexamined one of the subjects in Sharf (Morphology) that is IsmDhamiá¿‘r (Pronoun). Ism Dhamiá¿‘r are words used as the pronouneither for the frst person, the pronoun for the second person or thepronoun for a third person. In this research, the author also outlinedthe subject by giving examples of sentences in a form of a chart or acolumn so that it will be easy to understand from the explanationand it would argue on people thought on the complexity of learningArabic. The author expected that this research could be additionalknowledge and references in learning the grammar of Arabic.